Chylothorax: a review of 18 cases. Issue 11 (November 1986) - Fairfax, A J; McNabb, W R; Spiro, S G
Abstract : Eighteen patients who had developed a chylothorax during a 25 year period, 1955-80, were reviewed. The chylothoraces occurred as a complication of cardiothoracic surgery in 11 patients, of whom eight were children in the first decade of life. Five cases followed operations for coarctation of the aorta and two occurred as a complication of a Blalock shunt for Fallot's tetralogy. The chylothorax was evident within 48 hours of the operation in all but two patients. In seven cases a second operation was performed to prevent further chylous leakage and in two infants the thoracic duct was ligated. The remainder of the postsurgical chylothoraces responded to either continuous drainage or repeated aspiration and a low fat diet. There were no late sequelae of chylothorax following surgery. Spontaneous chylothorax was identified in seven patients and in five of these it was bilateral. Patients with spontaneous chylothorax were all adults and, despite treatment, had a poor prognosis. Three with malignant disease and two with pulmonary lymphangioleiomyomatosis had died within two years of the appearance of the chylothorax. Two patients with chronic idiopathic chylothoraces survived for more than two years and one of these developed a secondary fibrothorax.